Hubungan Tingkat Pendidikan dengan Perilaku Kepatuhan 3M dalam Upaya Pencegahan Penularan COVID-19 pada Era New Normal - Sasteri Yuliyanti; Supriadi, Supriadi; Suhaemi, Suhaemi (STIKes Hamzar, 2022)
Background: Corona Virus Disease or Covid-19, appeared for the first time in Wuhan City of China in 2019. The spread of the corona virus from human to other humans is very quick and aggressive. The most effective way to overcome and prevent this pandemic is to break the chain of Covid-19 transmission by implementing 3M's health protocols in a disciplined manner. Purpose: To find out the relationship between education level and 3M's compliance behaviour in a way to prevent the transmission of Covid-19 in the New Normal Era at the Sakra Health Centre.Methods: This research was conducted by using a quantitative observational analytic approach with a cross-sectional design. The sample was 100 respondents who visited the Sakra Health Centre by using the accidental sampling technique. The Analysis of the data was Rank Spearman.Results: The highest level of community education in this study was from the secondary education level group, as many as 44 respondents (44%). The highest level of community compliance in this study was from a group that had a moderate level of compliance as many as 40 respondents (40%). Based on the results of statistical tests using the Spearman Rank test, a significant value was obtained for p value = 0.000 <0.05 with a value of (r) rho = 0. 724. Conclusion: There is a significant relationship between education level and 3M's compliance behaviour in way to prevent Covid-19 transmission in the new normal era at the Sakra Health Centre.